AB0645 Puffy Fingers Usually Point at Microvascular Damage. (10th June 2014) - Recuero, S.; Romero-Bueno, F.I.; Franco, C.; Pérez-Esteban, S.; Bermúdez, S.; Martínez-Becerra, M.J.; Herrero-Beaumont, G.; Sanchez-Pernaute, O.
Abstract : Background: Nailfold capillaroscopy (NC) can predict progression to systemic sclerosis (SSc) in patients diagnosed with primary Raynaud's phenomenon (RP). The occurrence of puffy fingers (PuFi) in patients with RP and positive antinuclear antibodies (ANA) has been associated to NC SSc-like lesions. The coexistence of these three factors has been recently proposed as criterium for very early SSc diagnosis. Objectives: In this study we have explored the NC features in patients with PuFi in a 1-year NC registry from our unit. Methods: Data were retrospectively collected from clinical records and from systematized NC evaluation sheets, which include a semiquantitative scoring, classification into established patterns of lesions, and description of coincidental macroscopic alterations. Data are shown as incidence rates. Statistical analysis was done with Chi-Square, Fisher's test and multivariate analysis. Results: 136 cases were included in the analysis. NC was considered pathologic in 73 cases (54% of the cohort, rising to 60% in RP+ patients, p 0.036). PuFi were present in 20% of all patients. A higher incidence of pathologic NC studies was observed in the PuFi+ group (78%, p 0.002). NC lesions in this subgroup of patients were classified as SSc-like (13 p), non-SSc CTD-like (7 p), and non-immmune vasculopathy (2 p). There was coexistence with RP in 20 PuFi+ cases, but it did not increase either the risk of having a pathologic NC study (81% in double positive patients vs 83% in PuFi+ without RP) or the appearance of a SSc-like NC pattern in the subgroup. The occurrence of PuFi showed a strong association with + ANA (77% vs 54% in PuFi- patients, p 0.029). Moreover, the presence of both traits strongly predicted NC alterations, which appeared in 0.9% of double negative cases, 73% of ANA+ patients alone, and 90% of double positive cases. Patients with PuFi were diagnosed with primary RP (3 p), SSc (11 p), mixed connective tissue disease (CTD) (1 p), dermato/polymiositis (4 p), and non-classifiable CTD (6 p), while no PuFi+ cases were found in primary Sjögren's syndrome, lupus, rheumatoid arthritis, vasculitis, or antiphospholipid syndrome. No specific microscopic features were associated to PuFi. Conclusions: In summary, in this cohort we have observed a high incidence of NC alterations in association with PuFi. Our findings support the relevance of PuFi as a CTD-associated trait, as recently underscored by the new EUSTAR proposed criteria for SSc classification. In addition, the appearance of ANA together with PuFi in our patients strongly predicted NC lesions, even in the absence of RP. Also of interest, PuFi were not exclusive of a SSc-like pattern of NC lesions. We suggest that NC should be performed in any patients presenting with a CTD-like scenario and swollen hands or PuFi, even in the absence of RP, because findings are likely to help characterize their syndrome. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3024